# Solve the system by elimination?

{3a+4b=9

{-3a-2b=-3

### 12 Answers

- PinkgreenLv 74 weeks ago
3a+4b=9------(1)

-3a-2b=-3-----(2)

(1)+(2)=>

2b=6=>

b=3

(1)+2*(2)=>

-3a=3=>

a=-1

The answer is

a=-1

b=3

- formengLv 64 weeks ago
First add the two equations to eliminate the variable "a."

3a + 4b = 9

-3a-2b =-3

----------------

2b = 6

b=3

Now, substitute the value of "b' into either equation.

3a + 4(3) = 9

3a = 9-12 (Subtract 4(3) = 12 from both sides of the equation.)

3a = -3

a= -1

Answer (a, b) = ( -1, 3)

- lenpol7Lv 74 weeks ago
Subtract the two equations. This will eliminate 'a'

Hence

2b = 6

b = 3

When b = 3

3a + 4(3) = 9

3a + 12 = 9

3a = -3

a = -1

- PhilipLv 64 weeks ago
3a+4b = 9...(1).;

-3a-2b = -3...(2).;

(1)--->3a=9-4b;

Substitute (9-4b) for the 3a in (2) getting -(9-4b)-2b = -3;

ie., 9-4b+2b=3;

ie., 9-2b=3;

ie., 2b=9-3 = 6;

ie., b = 3;

Then (1)---> 3a = 9-12 = -3;

ie., a = -1.;

- What do you think of the answers? You can sign in to give your opinion on the answer.
- la consoleLv 74 weeks ago
(1) : 3a + 4b = 9

(2) : - 3a - 2b = - 3

You calculate (1) + (2)

(3a + 4b) + (- 3a - 2b) = 9 + (- 3)

3a + 4b - 3a - 2b = 9 - 3

2b = 6

→ b = 3

Recall (1) : 3a + 4b = 9

3a = 9 - 4b → where: b = 3

3a = - 3

→ a = - 1

- Anonymous4 weeks ago
Surprising how many people get their education on Yahoo! Answers. Could be why the world is so screwed up nowadays.If you can't cook, get out of the kitchen.

- Engr. RonaldLv 74 weeks ago
{3a+4b=9 ... eq1

{-3a-2b=-3 .. eq2

----------------

2b = 6

b = 3 Answer//

solving for a from eq1

3a + 4b = 9

3a + 4(3) = 9

3a + 12 = 9

3a = 9 - 12

3a = - 3

a = - 1 answer//

- Jeff AaronLv 74 weeks ago
Add the equations:

2b = 6, so b = 6/2 = 3

Multiply the second equation by 2:

-6a - 4b = -6

Add that to the first equation:

-3a = 3

a = 3/(-3) = -1